THE GENUS ACIOA Aublet (Rosaceae - Chrysobalanoideae) IN MALESIA - A. J. G. H. KOSTERMANS (Reinwardtia, 1965)
The first record of Aciov, Aublet from S.E. Asia.Three species are described: Acioa heteropetala (Scortechini ex King) Kosterm.,based on Parinarium heteropetalum Scortechini ex King and the new species:Acioa malayana Kosterm. and A. percoriacea Kosterm.Parinwrium kunstleri King and P. myriandrum Merr. are reduced to synonymy of Acioa heteropetala Kosterm.